lim n → ∞ n 3 1 2 + 2 2 + 3 2 + . . . + n 2 can be expressed in the form b a . Find a + b
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good solution!
1 2 + 2 2 + 3 2 +....+ n 2 = 6 n (n+1)(2n+1).
6 n (n+1)(2n+1)/ n 3 = 6 1 (1)(1+ n 1 (2+ n 1 ). When n tends to infinity, both n 1 and n 2 tend to 0 so we have 6 2 = 3 1 as the limit. Now a+b = 1+3 = 4
n 3 ∑ k = 1 n k 2 = 6 n 3 n ( n + 1 ) ( 2 n + 1 ) = 6 n 2 2 n 2 + 3 n + 1 n → ∞ lim 6 n 2 2 n 2 + 3 n + 1 = ∞ ∞ Apply L'Hôpital's rule twice: n → ∞ lim 6 n 2 2 n 2 + 3 n + 1 = n → ∞ lim 1 2 n 4 n + 3 = n → ∞ lim 1 2 4 = 3 1 1 + 3 = 4
n → ∞ lim n 3 1 2 + 2 2 + 3 2 + … + n 2 = n → ∞ lim n 1 k = 1 ∑ n ( n k ) 2 = ∫ 0 1 x 2 d x = 3 1 ∴ a + b = 4
I posted this same problem before. This came from the Piskunov calculus book, I think.
Problem Loading...
Note Loading...
Set Loading...
Using 1 2 + 2 2 + 3 3 + . . . + n 2 = 6 n ( n + 1 ) ( 2 n + 1 ) : n → ∞ lim n 3 1 2 + 2 2 + 3 2 + . . . + n 2 = n → ∞ lim 6 n 3 n ( n + 1 ) ( 2 n + 1 ) = n → ∞ lim 6 n 2 2 n 2 + 3 n + 1 = 6 n 2 2 n 2 = 3 1 ∴ a + b = 4 Note that I got rid of the smaller powers of n because they become insignificant compared to n 2 as n tends to infinity.